The Efficacy of Temu Putih Fraction (Curcuma Zedoaria (Berg) Roscoe) Related Quality and Quantity of Spermatozoa in Male Wistar Rats - Tiara Fatrin; Salni Salni; Sri Nita; Rachmat Hidayat; Triwani Triwani; Joko Marwoto; Ziske Maritska; Mgs Irsan Saleh; Nita Parisa; Nia savitri Tamzil; Evi Lusiana; Ayeshah Agusta Rosdah (HM Publisher, 2017)
Background Male participation in KB is still relatively low when compared to the participationof women. Researchers have to do research to find the contraception drug. Temu putih (Curcuma Zedoaria (Berg) Roscoe) is one of traditional herb that used as antifertility. Aim of Study Aim of this study to examine change in the amount, motility, morphology, and viability spermatozoa male rats (rattus norvegicus) due to temu putih fraction suplementation. Methods This study was an experimental study using a completely randomized design (CRD), post test with control group design. The sample in this study was 30 male rats, 10 weeks old, weight 150-200 gram. Rats were given temu putih fraction (n hexan, etylacetate and methanol-water) at dose of 300 mg/kgBB/day for 48 days. Temu putih was extracted by ethanol and did fractionation by liquid-liquid methods. The results of this study were assayed by SPSS 18. Results The amount, motility, morphology and viability of spermatozoa in the group of metanol fraction of water decreased compared with the control group (p= 0,000), motilitas of spermatozoa in the group of metanol water fraction decreased compared with the control group. Conclusion Temu putih fraction can reduce the amount, motility, morphology, and viability of spermatozoa in male rats. Keywords: Fraction, Temu Putih, Amount of spermatozoa, Motility of spermatozoa, Viability Of Spermatozoa